Hypothetical syllogistic and Stoic logic - Speca, Anthony. (Philosophia Antiqua, 2001)
This volume traces the development of Aristotle's hypothetical syllogistic through antiquity, and shows for the first time how it later became misidentified with the logic of the rival Stoic school. By charting the origins of this error, the book illuminates elements of Aristotelian logic that have been obscured for almost two thousand years, and raises important issues concerning the distinctive roles of semantic and syntactic analysis in theories of logical consequence. The first chapters of the book deal with the original Aristotelian hypothetical syllogistic, and explain how Aristotle's later followers began to conflate it with Stoic logic. The final chapters examine in detail the two most crucial surviving treatments of the subject, Boethius's On hypothetical syllogisms and On Cicero's Topics , which carried this conflation into the Middle Ages.